EFFECTIVE MODELING OF THE EDUCATIONAL PROCESS BASED ON THE MECHANISM OF APPLYING EDUCATIONAL METHODS - Malokhat Ergashevna Akhmedova (Journal Park Publishing, 2025)
The development of pedagogical skills in higher education is based on enhancing the educational and upbringing process of future teachers. The core role belongs to the system of pedagogical sciences, including pedagogy, its theory and history, modern pedagogical technologies, pedagogical mastery, and psychology. These disciplines not only provide fundamental knowledge but also broaden the worldview and methodological competence of prospective teachers. Pedagogical skills are strengthened during teaching practice, where students acquire and test practical abilities. Social and pedagogical activity also plays a crucial role, as its scope and quality directly affect effectiveness. Ultimately, the most efficient way to achieve pedagogical mastery is through self-education, since teaching itself is a creative field that requires continuous exploration and innovation.
Keywords: Pedagogical activities, self-education, upbringing technologies, methods, traditional methods and diagnostic methods, document analysis method, experimental method , questionnaire (interview) method, independent characteristics method, biographical method and pedagogical skills.